La formule ou comment la philosophie l’attrape - Richard Pedot (Transatlantica)
This paper focuses on philosophical reading of fiction, namely “Bartleby the Scrivener”, famously interpreted by Deleuze in his “Bartleby, ou la formule”, which is in turn criticized by Jacques Rancière. It purports to show how philosophy is seduced by Bartleby / “Bartleby”’s formula, being unable to tell apart poetical and philosophical formulæ.